The Association between Obesity and Premenopausal Breast Cancer According to Intrinsic Subtypes – a Systematic Review - Torres-de la Roche, Luz Angela; Steljes, Isabell; Janni, Wolfgang; Friedl, Thomas W. P.; De Wilde, Rudy Leon (Geburtshilfe und Frauenheilkunde, 2020)
Introduction Obesity is a well-established risk factor for postmenopausal hormone-receptor positive breast cancer. The relationship between premenopausal breast cancer intrinsic subtypes and obesity is not completely elucidated; therefore, this systematic review was conducted to give an overview about the existing evidence.Methods This review followed the PRISMA Statement for Systematic Reviews and Meta-analyses. Full electronic search was conducted in PubMed and Orbis for articles published in English between January 2008 and June 2018. The literature search was performed in June 2018 using search strings that combined the Medical Subject Headings (MeSH terms) keywords and/or text words in any field were used: “body mass index” (BMI) OR obesity OR overweight AND premenopausal breast cancer.Results 391 articles were found to be eligible, of which ultimately 21 were included comprising a total of 55 580 breast cancer patients. 45% were case-control studies, 35% were single cohort studies, 15% were cohort studies, two were cross-sectional studies, one was a multicenter-study and one was a pooled analysis. The evidence shows a tendency for an increased risk for the more aggressive triple negative breast cancer subtype in obese premenopausal women and a decreased risk for less aggressive tumor subtypes such as the luminal A subtype. The evidence is limited by small sample sizes for triple negative and HER2-positive subtypes in severely obese patients.Conclusion Higher BMI might influence aggressive tumor characteristics among premenopausal women and has divergent impacts on the risk of different breast cancer subtypes. Further research is needed to confirm these results and to evaluate potential pathophysiologic mechanisms for the relationship between obesity and aggressive premenopausal breast cancer subtypes.
Keywords: hormone receptor; premenopause; breast neoplasms; receptors; obesity; risk factors